Social networks, social support and social negativity: A qualitative study of head and neck cancer caregivers' experiences. (22nd December 2016) - Balfe, M.; Keohane, K.; O'Brien, K.; Sharp, L.
Abstract : Head and neck cancer is a serious form of cancer that can generate substantial physical and psychosocial morbidity. Informal caregivers can help patients to manage head and neck cancer and its emotional impacts, both during and after treatment. Caregivers, however, can experience considerable stress as a result of their caring activities. Supportive relationships can protect caregivers from psychosocial strain. Thirty‐one head and neck cancer caregivers were interviewed about their experiences of accessing social support from their social networks; difficulties that they experienced accessing this support; and strategies that they used to address these difficulties. Results suggest that head and neck cancer caregivers strongly value social support, but can find it difficult to obtain, and a number of them experience socially negative responses from their networks. Some carers attempt to answer or supplement support deficiencies by turning to non‐human coping supports, such as pets, spiritual figures or medication. Implications for theory and practice are discussed.